P3 3 Creeper Cataclysm for Lunar Destruction - Purushu, Pooja; Alcock, Ellie; McNaughton, Tom (Physics Special Topics, 2024)
This paper investigates the explosive power of a Creeper in the popular game of Minecraft, and utilises it to calculate how many Creepers would be required to destroy the Moon. The explosive power of a Creeper and the blinding energy of the Moon were calculated to be 11.66 MJ and U_grav= 1.24 × 10^29 J respectively. Thus, in order to blow up the Moon, 1.07 × 10^22 Creepers would be needed.